A COMPARATIVE STUDY TO FIND OUT THE DIFFERENCES IN ACADEMIC STRESS AND ITS IMPACT ON ACADEMIC PERFORMANCE BETWEEN HUMANITIES AND COMMERCE STUDENTS - Mrs. Licy Varghese (Galaxy International Interdisciplinary Research Journal, 2022)
In the present time, academic stress has become a major challenge for the students that affect their academic performance. In this article, we will compare the academic stress of the students belonging to humanities and commerce streams. Competition among the students in the present era is increasing to improve their academic performance to make a good place in society. Making a good place in society creates a lot of pressure on the students that affect their academic performance of the students. Stress is defined as the process that affects the mind of people by responding to a threatening event. Academic stress puts the students into depression, anxiety, and frustration. Stress creates an uncomfortable emotional experience due to physiological biochemical and behavioral changes in the mind. Learning is considered very important for improving the academic excellence of the students. It is very common for adolescents to experience academic stress from time to time.